The Analysis of Students' Conceptual Comprehension Ability on Trigonometry Material at SMA Negeri 1 Raya Kahean - Cici Puspaningrum; Nanda Tia Losi (Study Program of Mathematics Education of Unimed Postgraduate Program, 2024)
This research aims to describe the mathematical concept comprehension abilities of 10th-grade students in Class X-3 at SMA Negeri 1 Raya Kahean, focusing on trigonometry. The study adopts a descriptive approach with a qualitative methodology, and subject selection is carried out through purposive sampling, involving 35 students. The research instruments include field observations and essay-based tests. The findings reveal that the mathematical concept comprehension abilities of Class X-3 students in trigonometry are categorized as high at 11.42%, moderate at 48.57%, and low at 40%.